(untitled) (Journal of Medicine, 2024)
Ossification of the posterior longitudinal ligament (OPLL) is a rare but potentially devastating clinical entity of degenerative myelopathy. Highest reported prevalence of OPLL is in East Asian countries. The cervical spine is more commonly affected followed by thoracic and lumbar spine. The clinical manifestations range from asymptomatic to myelopathy or myeloradiculopathy. Although rare, thoracic OPLL is more severe than cervical OPLL and usually requires operative intervention. CT scan is the investigation of choice to determine the extent and thickness of the ossification. Treatment ranges from observation in patients with minimal symptoms to Surgical decompression followed by stabilization for patients with myelopathy. Here we discuss a middle-aged lady who presenting with a slowly progressive spastic paraplegia with bladder dysfunction, without sensory involvement. She was being treated conservatively as a case of spondylotic degenerative disease, but showed no improvement. Finally proper evaluation of her radiologic finding and clinical correlation revealed the diagnosis of OPLL. She underwent laminoplasty with decompressive surgery. The outcome was proved to be curative. J MEDICINE 2024; 25: 179-183